Evaluation of liver stiffness on elastography ultrasound - S Vinoth Kumar (International Journal of Health and Clinical Research, 2021)
Introduction: Liver stiffness (LS) assessed by Ultrasound elastography can safely replace liver biopsy in several clinical scenarios, particularly in patients with chronic viral hepatitis. However, an increase of LS may be due to some other clinical conditions not related to fibrosis, such as liver inflammation, acute hepatitis, obstructive cholestasis, liver congestion, infiltrative liver diseases.Material and Methods: This is a prospective, observational study that was conducted in patients with impaired hepatic enzymes. Study conducted at Tertiary care teaching hospital over a period of 1 year. Inclusion criteria: Patients of either gender between age group 30 to 60 years. Elevated liver enzymes.Exclusion criteria: Biopsy samples smaller than 15 mm. Hepatic transplant patients in last 6 months. Coagulation disorders and risk of bleeding following biopsy. Patients with biopsy results did not meet the required quality criteria.Result: In our study, maximum number of patients were male 62 (68.8%) and least were female 28 (31.2%) in our study. The METAVIR fibrosis grades were as follows: F0-F1 = 43 (47.7%); F2 = 20 (22.2%); F3 = 13 (14.4%); F4.1 = 9 (10%); F4.2 = 5 (5.5%). In our study 27 patients experienced one or more Liver-related events; the first Liver-related events were: 23 hepatic decompensations (4 variceal bleeding, 4 ascites, 6 Hepatic encephalopathy, 5 Jaundice, 2 Hepatorenalsyndrome and 2 Spontaneous bacterial peritonitis), 2 hepatocellular carcinomas. Conclusion: Liver stiffness by Elastography accurately predicts the risk of death or hepatic complications in patients with chronic liver disease. TE may facilitate the estimation of prognosis and guide management of these patients.